Poets and Puppets: Interarts Collaboration in Alfred Kreymborg’s Lima Beans - Yasna Bozhkova (Transatlantica)
This article focuses on a little-explored case of modernist collaboration situated at the crossroads between different arts: the performance of Alfred Kreymborg’s play Lima Beans, produced by the Provincetown Players in December 1916, in which poets Mina Loy and William Carlos Williams played the two leading parts, together with poet and artist William Zorach, who also designed the sets. The play’s novel aesthetics breaks with the principles of the realist dramas typical of the time and favored even by more experimental groups like the Provincetown Players. First, the article examines how the play creates a distancing effect towards the deliberately mundane story of a married couple, using incongruous elements like the proto-absurdist nonsense of the dialogues, the abstract, Futurist sets, and the groundbreaking acting techniques inspired by puppet theater. Second, it specifically focuses on the blurring of the boundaries between the different arts—drama, poetry, and dance among others—in this play, whose dialogues were conceived as free verse. Finally, it delves into the intertextual and intermedial dialogues between the play and Loy’s and Williams’s poems published in the little magazine Others, edited by Kreymborg.